Obstruction of Justice Against Advocates in Indonesian Corruption Cases: Implications of Article 21 for Professional Independence - I Made Suardana; Sagung Putri M.E Purwani (International Journal of Science and Environment (IJSE), 2026)
The offense of obstruction of justice (OJ) functions to safeguard the integrity of the administration of justice from acts that intentionally interfere with law enforcement processes. In the context of corruption eradication in Indonesia, the regulation of OJ under Article 21 of the Anti-Corruption Law is designed as a protective instrument for the judicial system. However, the elastic formulation of the norm—particularly the phrase “directly or indirectly”—creates significant legal problems when applied to advocates, who are doctrinally positioned as independent officers of the court. This article examines the boundary between legitimate adversarial defense and obstruction of justice committed by advocates in the legal representation of corruption cases by analyzing the structure of the offense, the relationship between actus reus and mens rea, and its implications for professional independence and the principle of fair trial. This research employs a normative juridical method using statutory, conceptual, and doctrinal approaches, supported by national and international literature review. The findings demonstrate that the lack of precision in defining the elements of conduct, causality, and the threshold of intent in Article 21 of the Anti-Corruption Law has the potential to obscure the boundary between lawful defense actions and criminal obstruction, thereby increasing the risk of overcriminalization and creating a chilling effect on advocacy practices. This article proposes a framework for normative reform through rule-sharpening and role-based screening liability approaches to ensure that the criminalization of obstruction of justice continues to function as a safeguard for the judicial system without undermining the independence of the legal profession and the right to effective legal representation.